Characterizing ADRs of Enfortumab vedotin and Erdafitinib in bladder cancer treatment: a descriptive analysis from WHO-VigiAccess - Huang, Yuanbin; Xu, Meiqi; Ma, Xinmiao; Wang, Wei; Shen, Chen; Liu, Fei; Chen, Zhiqi; Wang, Jiawen; Guo, Qian; Li, Xiancheng (Frontiers in Pharmacology, 2024)
Introduction: Enfortumab vedotin (EV) and Erdafitinib are effective therapeutic drugs for bladder cancer patients following post-chemotherapy and immunotherapy. This study assessed adverse drug reactions (ADRs) from both drugs, comparing their safety profiles to guide clinical use. Methods: A retrospective descriptive analysis was conducted on ADR reports for EV and Erdafitinib from the World Health Organization (WHO)-VigiAccess database. Data on patient demographics, system organ classes (SOCs), global patient regions, symptoms, and ADRs frequencies were analyzed and compared. Results: As of 2024, 3,438 ADR reports were identified (2,257 for EV and 1,181 for Erdafitinib). The number of adverse reaction reports for EV is significantly higher than that for Erdafitinib. Among them, the SOC with the most adverse signals is gastrointestinal disorders, with the top five reports being nausea, gastrointestinal disorders, dry mouth, abdominal pain, and diarrhea. The top five reported adverse events (AEs) for EV are as follows: skin and subcutaneous tissue disorders (20.70%), general disorders and administration site conditions (14.23%), nervous system disorders (11.12%), gastrointestinal disorders (7.78%), and metabolism and nutrition disorders (6.47%). In contrast, the top five AEs for Erdafitinib are: general disorders and administration site conditions (25.36%), skin and subcutaneous tissue disorders (10.94%), gastrointestinal disorders (10.19%), eye disorders (9.21%), and injury poisoning and procedural complications (7.31%). Conclusion: Our study identified and compared potential and novel ADRs between EV and Erdafitinib, providing key insights into their safety profiles and highlighting the need for personalized treatment strategies based on individual patient risk factors.